Phytoplankton Composition and Distribution in the Coastal Area of Bachok, Kelantan. - Salleh, Aishah; Ruslan, Nur Diyana (Malaysian Journal of Science, 2010)
A study on the biodiversity of phytoplankton was carried out at Bachok, Kelantan from 14th to 18th June 2008. The objective of the study was to document the phytoplankton biodiversity of this scientifically little known area. Twenty genera and 54 species from two major divisions, Bacillariophyta (diatom) and Pyrrophyta (dinoflagellate) were recorded. Diatoms were richest and most diverse, with 51 species from 18 genera. The dominant diatoms were Chaetoceros constrictum, Rhizosolenia alata, Rhizosolenia bergonii and Rhizosolenia hebatata. Recorded salinities ranged from 14.44ppt to 33.6ppt, and pH from 7.17 to 8.07. ABSTRAK Kajian mengenai biodiversiti fitoplankton telah dijalankan di Bachok, Kelantan bermula dari 14 hingga 18 Jun 2008. Objektif kajian ini adalah untuk mendokumentasikan biodiversiti fitoplankton dalam kawasan yang kurang maklumat saintifiknya. Dua puluh genus dan 54 spesies dari dua divisi utama, Bacillariophyta (diatom) dan Pyrrophyta (dinoflagelat) telah direkodkan. Diatom paling banyak ditemui dengan taburan tertinggi dengan 51 spesies dari 18 genus. Dominan diatom adalah Chaetoceros constrictum, Rhizosolenia alata, Rhizosolenia bergonii dan Rhizosolenia hebatata. Kepekatan saliniti direkodkan dari 14.44ppt hingga 33.6ppt, dan pH dari 7.17 hingga 8.07. (Keywords: phytoplankton, biodiversity, Bachok, IOES)